Epidemiology, clinical characteristics, and outcomes of nontuberculous mycobacterial skin, soft tissue, and bone infections from a single center over a 10-year period - Mary B. Ford; Jason F. Okulicz; Jesse R. Salinas; John L. Kiley (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2023)
Introduction: Non-tuberculous mycobacteria (NTM) cause a wide variety of clinical syndromes. Data guiding diagnosis and treatment of NTM skin and soft tissue infections (SSTI) and bone infections are limited. We sought to better understand SSTI and bone infections caused by NTM. Methods: All NTM clinical isolates recovered at Brooke Army Medical Center from 2012 to 2022 were screened; SSTI and bone isolates were included. Electronic health records were reviewed for epidemiologic, microbiologic, and clinical data. Infections were defined as recovery of one or more NTM isolate from skin, soft tissue, or bone cultures with a corresponding clinical syndrome. Results: Forty isolates of skin, soft tissue, or bone origin from 29 patients were analyzed. Twenty (69 %) patients, majority female (14/20, 70 %), had infecting isolates, most commonly secondary to surgery (35 %) or trauma (35 %). Six of 20 (30 %) had bone infections. Time from symptom onset to isolate recovery was a median 61 days (IQR 43–95). Eight (40 %) had combined medical/surgical therapy, 8 (40 %) had surgery alone, and 4 (20 %) had medical therapy alone. M. abscessus was more frequently isolated from patients with true infections. Conclusions: Data supporting diagnosis and treatment decisions in NTM SSTI/bone infections is sparse. In this study the majority of NTM isolated were true infections. We confirm that surgery and trauma are the most common routes of exposure. The delay between symptom onset and directed therapy and the wide variety of treatment regimens highlight a need for additional studies delineating criteria for diagnosis and treatment.